An Invisible Wall: The Relationship Between Congregational and Seminary Libraries in the United States - Rebecca Klemme Eliceiri (Theological Librarianship, 2013)
Theological (seminary) and congregational libraries in the Christian and Jewish religious traditions have coexisted in some fashion since their beginnings; however, little research exists regarding the relationship between these related-but-distinct library types. This essay explores the relationship between these types of libraries through a survey of their literatures and available statistics, considering their histories and contexts within the broader religious and library worlds, as well as their current relationship in light of their diverse religious institutions. The roles of these libraries will be examined regarding religious, theological, and information literacies as well as exploring their staffs, their staff's education, funding, library hours, their goals, objectives, and outcomes, particularly regarding the changing landscape of religious and theological education for both clergy and laypeople.  It concludes with future possibilities in the religious library world in a congregational landscape that often cannot afford full-time, traditionally-theologically-educated clergy, much less paid congregational librarians.